What can be learned about caregivers in Canada from the analysis of families claiming the Canada caregiver credit? - Sung-Hee Jeon; Yuri Ostrovsky (Economic and Social Reports)
According to the 2018 General Social Survey (GSS) data on caregiving in Canada, one in four Canadians aged 15 and older have provided some form of care for people with a long-term health condition, a disability or problems related to aging. The main objective of this study is to use nationwide administrative data to spotlight Canadian families caring for family members (including extended family members) who have severe and prolonged impairments in physical or mental functions. More specifically, this study documents the prevalence of families claiming the Canada caregiver credit (CCC) among all tax-filing families and breaks down the results by several essential family characteristics.